Student Involvement as a Competency Catalyst: Uncovering the Influence of Infrastructure Management and Teaching Quality - Arif Mahmud; Heri Yanto; Sungkowo Edy Mulyono (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This study focuses on the influence of infrastructure management and teacher teaching quality on student engagement and its impact on student competence in Vocational High Schools (SMK). The main objective of this study is to analyze how the two factors work synergistically in improving student engagement and their competence. The research method used is a quantitative approach with an ex post facto type, where data is collected through a questionnaire distributed to 177 grade XI students majoring in Automotive Light Vehicle Engineering at several vocational schools in Salatiga. Data analysis was carried out using Structural Equation Modeling (SEM) to test the causal relationship between the variables studied. The results show that the management of infrastructure facilities and the quality of teachers' teaching have a significant effect on student engagement, which in turn improves their competence. The implications of this study emphasize the importance of a holistic approach in education management, where school managers must pay balanced attention between improving the quality of teaching and managing infrastructure facilities to create an optimal learning environment.